USDA SMOKING BAN - GIAMBERARDINO,M (Tufts Archival Research Center, 2007)
Memo from Marco Giamberardino to John Hoel on USDA Smoking Ban. Details policy of Property Management Division of USDA banning smoking inside all USDA facilities and motor vehicles and dictating any outside smoking areas must be at least 15 feet away from entrances and exits. Explains relationship to GSA regulation. Lists federal agencies with smoking bans.